Multi-Symplectic Fourier Pseudospectral Method for a Higher Order Wave Equation of KdV Type (Journal of Computational Mathematics, 2018)
The higher order wave equation of KdV type, which describes many important physicalphenomena, has been investigated widely in last several decades. In this work, multi-symplectic formulations for the higher order wave equation of KdV type are presented,and the local conservation laws are shown to correspond to certain well-known Hamiltonianfunctionals. The multi-symplectic discretization of each formulation is calculated by themulti-symplectic Fourier pseudospectral scheme. Numerical experiments are carried out,which verify the efficiency of the Fourier pseudospectral method.